34 Ethnic and Gender Differences in Symptom-to-Door Times in Patients Presenting with St Elevation Myocardial Infarction. (31st May 2014) - Brown, Richard; Shantsila, Eduard; Varma, Chetan; Lip, Gregory
Abstract : Introduction: Studies have shown higher in-hospital mortality for female patients and ethnic minorities admitted to hospital with acute ST elevation myocardial infarction (STEMI). Pre-hospital delay is associated with increased in-hospital mortality. We assessed the impact of gender and ethnicity on symptom-to-door-time in patients presenting with STEMI. Method: We conducted a retrospective study of our local British Cardiovascular Intervention Society (BCIS) database to determine symptom-to-door-times of consecutive patients receiving primary percutaneous coronary intervention (PPCI) between January 2008 and January 2013.Multivariate analysis was used to adjust for age, ethnicity (in the female population) and gender (between the ethnic groups). In hospital mortality was examined. Results: Of 1020 consecutive patients 768 (75%) were male (Table 1 ). South Asian (n = 263) and Afro Caribbean (n = 38) patients were more likely to be diabetic and younger than White-European patients (n = 719) (Table 2 ). Women were more likely to be diabetic and older than males (p = 0.019 and <0.001 respectively). They were also less likely to smoke or have a family history of coronary artery disease (CAD) (p = <0.001 and 0.039 respectively). The crude symptom-to-door times showed no relation to ethnicity (p = 0.37). On linear regression analysis after adjustment for age and gender, South Asian (SA) ethnicity was independently associated with later presentation than other ethnic groups (beta = –0.066 p = 0·037). On multivariate logistic regression analyses South Asian ethnicity was associated with higher in-hospital mortality after adjustment for age and gender (odds ratio [OR] 0.48 95% CI 0.26–0.87, p = 0.015) and after further adjustment for symptom-to-door times (OR 0.49, 95% CI 0.27–0.90, p = 0.022). In-hospital mortality was significantly higher in females (p = <0.001) however after adjustment for age and ethnicity symptom-to-door time was not significantly different between the sexes (p = 0.066). Conclusions: After adjusting for age and gender South Asians with STEMI present later following the onset of symptoms than other ethnic groups which may contribute to the higher in-hospital mortality seen in this group. There is no difference in symptom-to-door-time between men and women therefore this is unlikely to contribute to the observed sex difference in inpatient mortality.